Implementasi Blue Economy di Wilayah Pesisir Kenjeran Surabaya - Hani Mukaromah; Lilik Rahmawati (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2023)
This study aims to explain the implementation of the blue economy concept in the Kenjeran coastal area of ​​Surabaya. This research uses a descriptive method with a qualitative approach. The type of data used is primary and secondary data. Primary data obtained from observation and interviews with informants. Secondary data comes from literature reviews on official government websites, previous research journals, scientific papers, and other literacy sources. The results of the study reveal that of the 4 principles and indicators that serve as a reference for implementing the blue economy concept in the Kenjeran coastal area of ​​Surabaya, there are 3 principles that have been implemented and 1 principle in the pursuit stage.